Increasing Proactive Work Behavior Among Teachers in Islamic Senior High School: The Role of Ethical Work Climate and Perceived Organizational Support - Pradesa, Hafid Aditya; Tanjung, Hasrudy; Agustina, Iin; Salleh, Nik Sarina Nik Md (Universitas Muhammadiyah Yogyakarta, 2023)
Educational institutions, such as Islamic high schools, face challenges in managing teacher performance, particularly in promoting proactive behavior. This study explores the impact of an ethical work climate characterized by principles of caring, instrumental independence, service, rules, and codes, as well as perceived organizational support (POS), on teachers' proactive behavior in Islamic senior high schools. The study includes a one-month convenience sampling period, with 104 teachers from Medan, North Sumatra, participating as respondents. Primary data was collected through the respondents' perceptions and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). Findings highlight that an ethical work climate has a greater influence on teachers' proactive behavior than POS. While perceived organizational support remains important, Islamic schools' unique cultural and religious context may elevate the significance of an ethical work climate. Teachers may perceive ethical guidelines and values as integral to their role and mission within the Islamic educational setting, leading to a more profound impact on their proactive engagement than the general perception of organizational support. The study concludes that the ethical work climate in Islamic senior high schools influences teachers' proactive behavior. It emphasizes the importance of fostering and maintaining an ethical work environment to support teachers professionally.